Avaliação da implementação da política de educação escolar indígena no território Tapeba (CE) Fortaleza 2011 - Correia, Sílvia Barbosa (2011)
The Global Family Protection and Assessment Service (PAIF) has a continuous character, and seeks to strengthen the family and community ties, prevent the rupture of those that are pre-existent and facilitate the access to services that insure given rights. It is offered by the Social Assistance Reference Center (CRAS), a reference unit used to carry out social assistance as a public policy within the Basic Social Protection Program established in several Brazilian municipalities. The objective of this research is to evaluate the event management of the Global Family Protection and Assessment Service in a determined municipality of the Metropolitan Region of Fortaleza, as well as the actions developed and enforced by its professionals, always observing the limits, possibilities and results of those actions and their relation to the directives established between the sectors involved. A qualitative research took place, associating bibliographical and documental studies, observations and interviews with professionals of higher education (social assistant and psychologist), currently engaged within the Social Assistance Reference Center, as well as the Coordinator of the unit. The results reveal that the municipality has made efforts to execute the actions of the Global Family Protection and Assessment Service. The team is able to implement the delimited actions within the legal marks. However, the limits imposed by the reduced size of the team and lack of transportation are factors that decrease the number of people that can be reached and the quality of the work when the socio-family follow up and monitoring of the actions taken is considered. The directive used between the active sectors is incipient as it is still based on a common sense perspective in which the execution of systematic reunions must be held to share information, establish partnerships for specific actions and announce forwarding‟s. All professionals are hired under a temporary employment status and the quantity of daily activities makes a deep analysis about the actions undertaken a difficult task.